Lemme try to answer that.
It's 3. If you want the steps, email me.
ownager@sbcglobal.net
2006-10-27 17:50:55
·
answer #1
·
answered by OwNaGeR 3
·
0⤊
0⤋
3
2006-10-28 01:18:16
·
answer #2
·
answered by shibunath s 1
·
0⤊
0⤋
Do what it says: First distribute the 2:
You get 2z + 6 -17= -1
Combine like terms to get: 2z - 9 = -1
add 9 to both sides: 2z = 10
Divide by 2 to solve for z = 5.
Since you now know the value of z, then just substitute it into:
3(z-4) = 3 ( 5-4) = 3*1= 3!!!!
The trick is to first find your value of z, then you can find your value of 3(z-4). I guess they just want you to work like a detective, first use the clues they give you, in this case the equation 2(z+3)-17= -1, and then solve for your value!
2006-10-28 01:11:37
·
answer #3
·
answered by memo 1
·
0⤊
0⤋
2(z + 3) - 17 = -1,
apply the distributive property
2z +6 -17 = -1
2z -11 = -1
2z = -1 + 11
2z = 10
divide both sides by 2
2z/2 = 10/2
z = 5
then what is the value of 3(z - 4)?
3(z - 4) = 3(5 - 4)
= 3(1)
= 3
2006-10-28 01:07:00
·
answer #4
·
answered by lazareh 2
·
0⤊
0⤋
2(z+3) - 17 = -1 add 17 to each side
2(z+3) = 16 divide both sides by 2
z+3 = 8 subtract 3 from each side
z = 5
Now plug 5 into your next formula
3(5-4) always perform the actions in the parentheses first
3 x 1 = 3
I hope all your questions are that easy! Good luck!
2006-10-28 00:56:54
·
answer #5
·
answered by naturally_urban 1
·
0⤊
0⤋
2(z + 3) - 17 = -1
2z + 6 - 17 = -1
2z - 11 = -1
2z = -1 + 11
2z = 10
z = 10/2
z = 5
3(z-4) = 3(5-4)
= 3(1)
= 3
2006-10-28 01:02:02
·
answer #6
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
Or you could do it the cool way;
2(z+3)=16
z+3=16/2=8
z+3-7=z-4=8-7=1
3(z-4)=3(1)=3
Why do it the hard way when you could just do that? Who cares what z equals!
2006-10-28 01:59:55
·
answer #7
·
answered by tgypoi 5
·
0⤊
0⤋
2(z+3)-17=-1
2z+6-17=-1
2z-11=-1
2z+z-11-1=z-1-1
3z-12=z-2
3(z-4)=z-2 Ans
2006-10-28 09:19:49
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
2(z+3)-17=-1.....original equation
2(z+3)=-1+17 => 2(z+3)=16........add 17 to both sidess
2z+6=16..........multipli 2 with (z+3)
2z=16-6 => 2z=10..........subtract 6 from both sides
2z=10 z=5........divided 2 from both sides.
A: z=5
2006-10-28 01:31:27
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
2z + 6 -17 = -1
2z + (6-17) = -1
2z + (-11) = -1
+(11) 2z + (-11) = -1 + (11)
2z = 10
divide each side by 2
z=5
3(5-4)
3(1)
the value of 3(z-4) would be 3...I think.
2006-10-28 00:52:56
·
answer #10
·
answered by SuzieQ 3
·
1⤊
0⤋
I keep coming up with z=5 but when I put that into the 3(z -4) I get a 3(5-4) so 15-12= 3 sorry but good luck! hey i got it right after all!!! solve for z then plug it into the second value question. thanks for waking up my brain....!!!!!(:
2006-10-28 03:12:18
·
answer #11
·
answered by cowboybabeeup 4
·
0⤊
0⤋